(untitled) (Nigerian Journal of Technology, 2018)
service delivery centered yardsticks like staff mix by rank and lecturer-to-student ratio. This leave management solution is intended to interface with a staff database, course registration system and a staff appraisal system. In working mechanism, it is an algorithm that assesses leave requests and schedules the leave requested for periods having least impact on staff mix by rank and lecturer-to-students ratio. In the Nigerian university system, leave can be managed to avail academic staff for training, research and even rest. In pursuance of these, human resource planners may overcommit staff to it, leaving the system understaffed at key moments, or under commit to it and lose out on the benefits. Either way, service delivery is adversely affected. The algorithm was developed following iterative incremental process model, in three increments, each executing their corresponding set of requirements. The algorithm was implemented using MATLAB. The work features generation of sample data of academic staff in a particular engineering degree program, sorting of that data into staff mix by rank, and then computation of available and recommended staff mix by rank given the number of students the engineering program has. The algorithm schedules leave for periods of least impact on service delivery of University academic staff by picking the year with the least shortfall in available staff mix considering the recommended staff mix. http://dx.doi.org/10.4314/njt.v37i4.25